Badania stratygrafii obrazów nowoczesnych na przykładzie twórczości Aleksandra Kobzdeja - Kamiński, Sławomir A.; Rozłucka, Zuzanna (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2011)
The authors, within the framework of a larger project, carried out examination of modern paintings by Aleksander Kobzdej. This paper comprises discussion on the technical structure of paintings by the artist mentioned above and the results of examination of the stratigraphy of selected paintings. The results of microscopic examination of cross sections of samples taken from those paintings are illustrated with photographs in visible and UV-light. The conclusions concern applicability of microscopic method of examining the stratigraphy of samples for investigating the structure of modern paintings. Applicability of the mentioned technique also in this field has been confirmed, provided that the following conditions are met: broadening photographic documentation of the location of collected samples – the role of macro-photographs, increasing the assortment of the methods of assessing the condition of paintings as well as broadening the spectrum of methods of examining the composition of synthetic substances – both artist’s materials and others.